ANALISIS KEBIJAKAN KEDUDUKAN JUSTICE COLLABORATOR DAN WHISTLEBLOWER DALAM TINDAK PIDANA KORUPSI - Bagus Diyan Pratama; Budiarsih Budiarsih (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The role of Justice collaborators and Whistleblowers is urgently needed to assist law enforcement officials in uncovering cases such as criminal acts of corruption, but on the other hand there is a big risk that must be borne by a Justice collaborator and Whistleblower, so it is very necessary to have legal certainty for Justice collaborators and Whistleblowers to provide a sense of security, comfort, and free from threats or intimidation and discrimination. The focus of the research is Policy Analysis on the Position of Justice Collaborators and Whistleblowers in Corruption Crimes. This study uses the method of normative legal research (legal research) and two approaches, namely the statutory approach (statute approach), conceptual approach (conceptual approach). The results of this study found that the policy positions of Justice collaborators and Whistleblowers in corruption cases found several problems, including first, the need for a common perception and synchronization of existing regulations for law enforcement officials in understanding aspects of witness protection. secondly, although there have been several arrangements regarding Justice collaborators and Whistleblowers, the Criminal Procedure Code still has no provisions that specifically, clearly and definitely regulate the protection of Justice collaborators and Whistleblowers. Such conditions result in less-than-optimal legal protection for Justice collaborators and Whistleblowers